2018
DOI: 10.9745/ghsp-d-17-00346
|View full text |Cite
|
Sign up to set email alerts
|

Family Planning in the Democratic Republic of the Congo: Encouraging Momentum, Formidable Challenges

Abstract: Formidable challenges: uncertain political situation, cultural norms favoring high fertility, a thin patchwork of service delivery institutions, logistical issues in a vast country with weak infrastructure, and low capacity of the population to pay for contraceptive services. Encouraging progress: increasing government and donor support, openness to progressive service delivery policies, innovative programming including robust social marketing and initiatives with nursing schools and the military, strong colla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 13 publications
3
36
0
Order By: Relevance
“…In Masisi, North Kivu, a 2013 assessment found that none of the 26 assessed public health facilities had a health worker trained to provide adolescent-friendly services; participants in focus group discussions stated that adolescent women were less likely than adult women to access contraceptive services [7]. This is consistent with other studies that also show that adolescent-friendly SRH services were limited nationwide [13,14].…”
Section: Introductionsupporting
confidence: 75%
“…In Masisi, North Kivu, a 2013 assessment found that none of the 26 assessed public health facilities had a health worker trained to provide adolescent-friendly services; participants in focus group discussions stated that adolescent women were less likely than adult women to access contraceptive services [7]. This is consistent with other studies that also show that adolescent-friendly SRH services were limited nationwide [13,14].…”
Section: Introductionsupporting
confidence: 75%
“…DMPA-SC is still relatively scarce in Kinshasa (available in only 27.8% of pharmacies and health facilities) [3] and, even then, at prices that many women cannot afford. The major social marketing program provides DMPA-SC but uses its own personnel (“bees”) to administer it [21] . Will local health centers allow women to purchase doses of DMPA-SC for home use without charging them the client inscription fee?…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the information gathered through the SDP survey was cross-sectional data and did not provide a comprehensive picture of the everchanging supply environment in Kinshasa. Most of the supply chain is managed by multiple donors and implementing organizations which procure and distribute commodities in parallel to national system supply chain channels [62]. This allows for a rapidly changing supply chain environment in which it is difficult to obtain comprehensive information regarding possible sources of contraceptive services.…”
Section: Discussionmentioning
confidence: 99%